(untitled) (Research, Society and Development, 2022)
Urban trees have become a fundamental element of landscapes and urban green composition, being essential in maintaining the environmental quality of cities, squares and schools, significantly interfering with microclimatic conditions. Thus, well-planned afforestation is very important, as there are several benefits regardless of the size of the city, as they are conditioned to the quality of life and its planning, otherwise, it starts to have a remedial character, as it tries to fit. within the existing conditions and solve problems of all kinds. The objective of the research was to make students aware that planting trees is important, including in the school environment and in the community around the school, so that there can be more commitment to the environment that they have come across. Thus, a project was carried out with 1st year students of afternoon high school, from the Pedro Joaquim de Jesus State School of Basic Education, located in the municipality of Teotônio Vilela, Alagoas, in November 2018. Based on the questions asked to the students, it was possible verify that their knowledge about the importance of afforestation was basic. However, over the course of the project, the students’ conception of the importance of plants changed, due to the action of the project. However, the work carried out made it possible to experience an experience by providing the students with knowledge on the theme of the importance of plants in the environment in which they live, in our ecosystem, making them aware of the care, maintenance and preservation of the environment and human health, the nature.